Different GABA(A) receptor subtypes mediate the anxiolytic, abuse-related, and motor effects of benzodiazepine-like drugs in primates - Rowlett, James K. (National Academy of Sciences, 2005)
Benzodiazepines exert their effects by binding to multiple subtypes of the GABA(A) receptor, the predominant subtypes in the brain being those that contain α(1)-, α(2)-, α(3)-, and α(5)-subunits. To understand the potentially different roles of these subtypes in the therapeutic and side effects of benzodiazepines, we evaluated GABA(A) receptor subtype-preferring compounds in nonhuman primate models predictive of anxiolytic, sedative, motor, subjective, and reinforcing effects of benzodiazepine-type drugs. These compounds included zolpidem, which shows preferential binding to GABA(A) receptors containing α(1)-subunits (α(1)GABA(A) receptors); L-838,417, which shows functional selectivity for α(2)GABA(A), α(3)GABA(A), and α(5)GABA(A) receptors; and nonselective conventional benzodiazepines. The results provide evidence in nonhuman primates that α(1)GABA(A) receptors do not play a key role in the anxiolytic and muscle-relaxant properties of benzodiazepine-type drugs; instead, these effects involve α(2)GABA(A), α(3)GABA(A), and/or α(5)GABA(A) subtypes. Our results also suggest that the α(1)GABA(A) receptor subtype might be critically involved in the subjective, sedative, and motor effects of benzodiazepine-type drugs. In contrast, stimulation of α(1)GABA(A) receptors is sufficient, but not necessary, for mediation of the abuse potential of these drugs.